Analysis of the teacher's difficulties in the preparation of teaching modules Kurikulum Merdeka in elementary school - Septi Yulaehah; Ratnasari Diah Utami (Inovasi Kurikulum, 2024)
The year 2023 is the second year of the implementation of Kurikulum Merdeka, but teachers are still unfamiliar with the curriculum transition. The purpose of this study is to find out which parts of the teacher have difficulty in compiling teaching modules and how efforts to overcome the challenges in compiling teaching modules. The method used is descriptive qualitative. The data source is selected by purposive sampling. The subject of this research is teachers who implement Kurikulum Merdeka, and the object is the teacher's difficulty in preparing the Kurikulum Merdeka teaching module. The data collection technique uses observation, interview, and documentation study methods. The data validity technique uses data and source triangulation techniques. The data analysis technique uses Milles & Huberman's interactive analysis model, which includes the stages of data collection, data reduction, data presentation, and conclusion drawing. This study's results indicate teacher difficulties in preparing teaching modules, namely, analyzing the conditions and needs of students, ATP analysis, determining time allocations, learning models and methods, learning objectives, meaningful understanding, and assessment. Efforts made by teachers in overcoming difficulties, namely, observation, asking about activities and learning that students like, discussing with peers, looking for references on the internet, opening an independent teaching platform, adjusting student needs and predicting the duration of activities, and targeting time for doing assignments.   Abtsrak Tahun 2023 merupakan tahun kedua diimplementasikannya Kurikulum Merdeka, namun guru masih belum terbiasa dengan adanya peralihan kurikulum tersebut. Tujuan penelitian ini untuk mengetahui pada bagian mana guru kesulitan dalam menyusun modul ajar dan bagaimana upaya untuk mengatasi kesulitan dalam menyusun modul ajar. Metode yang digunakan kualitatif deskriptif, sumber data dipilih secara purposive sampling. Subjek penelitian ini adalah guru yang menerapkan Kurikulum Merdeka, dan objeknya adalah kesulitan guru dalam penyusunan modul ajar Kurikulum Merdeka. Teknik pengumpulan data menggunakan metode observasi, wawancara, dan studi dokumentasi. Teknik keabsahan data menggunakan teknik triangulasi data dan sumber. Teknik analisis data menggunakan model analisis interaktif Milles dan Huberman yang meliputi tahapan pengumpulan data, reduksi data, penyajian data, dan penarikan kesimpulan. Hasil penelitian ini menunjukkan adanya kesulitan guru dalam menyusun modul ajar yakni; menganalisis kondisi dan kebutuhan peserta didik, analisis ATP, menentukan alokasi waktu, model dan metode pembelajaran, tujuan pembelajaran, pemahaman bermakna, asesmen. Upaya yang dilakukan guru dalam mengatasi kesulitan yakni; observasi, menanyakan kegiatan dan pembelajaran yang disukai peserta didik, berdiskusi dengan teman sejawat, mencari referensi di internet, membuka platform merdeka mengajar, menyesuaikan kebutuhan murid dan memprediksi lama durasi kegiatan, menentukan target waktu mengerjakan tugas. Kata Kunci: Kesulitan guru; kurikulum merdeka; modul ajar; sekolah dasar